Ammonia Reflections on Unmodified Seaweed, Euchuema Sp. as Biosorbent of Wastewater - Musa, Sabariah (International Journal of Integrated Engineering, 2019)
In wastewater, the high concentration of ammonia nitrogen that exceeds the standard effluent can give detrimental effects to the environment such as eutrophication. The conventional method for ammonia nitrogen removal often requires high cost. The main objective of this paper is to reduce the ammonia nitrogen level in wastewater effluent for fulfill the compliance in Environmental Quality Act (1974). Biosorption method was used as the ammonia nitrogen removal by using seaweed, Euchuema sp. Batch study was conducted by optimizing the biosorbent dosage and pH in wastewater samples. The seaweed from Eucheuma sp. which is a marine algae species was used as a biosorbent. The effectiveness of ammonia nitrogen ammonia removal was tested with different dosage of Euchuema sp., with 0.1 g, 0.2 g, 0.3 g, 0.4 g, and 0.5 g. The optimisation study shows the satisfactory effective for the biosorbent dosage at 0.3 g and pH 6 with removal of 49.1% of ammonia nitrogen. Therefore, it is deduced that Euchuema sp. has a potential as biosorbent but further treatment is needed to secure highest removal of ammonia nitrogen. Thus, it is shows that the wastewater effluent is safelytreated and can be discharged to the nearest river directly and will not be harmful towards the environment, human being and aquatic life.